(untitled) (Bangladesh Journal of Botany, 2021)
Ecological study of epiphytic ferns growing on bamboo species in Bogor Botanic Gardens, a man-made ecosystem located in a wet lowland area was carried out. The 350 phorophytes of 35 bamboo clumps belonging to 9 species and 3 genera were observed. Each culm was divided into intervals of 1 m from ground level to a height of 3 m. A total of 1984 individuals belonging to 12 species, nine genera, and six families of epiphytic ferns were recorded, with the highest species richness in Polypodiaceae (7 spp.). Dendocalamus giganteus Munro was the best host for epiphytic ferns (9 spp.). Two dominant species, Asplenium nidus L. and Davallia denticulata (Burm.f.) Mett. ex Kuhn with the same frequency value (97.14%), and relative species abundance of 31.49 individuals per clump and 14.94 individuals per clump, showed the highest Importance Value Index (IVI) of 83.19 and 54.00%, respectively. The first one-meter level of bamboo culms hosted all the species. Pyrrosia piloselloides (L.) Price was the only species that grew until the highest intervals of height with a decreasing frequency from the bottom. Bangladesh J. Bot. 50(4): 1095-1107, 2021 (December)